2023
DOI: 10.1002/alz.13411
|View full text |Cite
|
Sign up to set email alerts
|

Novel methodology for detection and prediction of mild cognitive impairment using resting‐state EEG

Abstract: BACKGROUNDEarly discrimination and prediction of cognitive decline are crucial for the study of neurodegenerative mechanisms and interventions to promote cognitive resiliency.METHODSOur research is based on resting‐state electroencephalography (EEG) and the current dataset includes 137 consensus‐diagnosed, community‐dwelling Black Americans (ages 60–90 years, 84 healthy controls [HC]; 53 mild cognitive impairment [MCI]) recruited through Wayne State University and Michigan Alzheimer's Disease Research Center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…The convergence speeds of CCM and cCCM also vary with the signals under applications and need to be taken into consideration in causality analysis, especially in dynamic systems where the causal relationships are time-variant. It is worthy to point out that when combined with the sliding window approach [47,48], cCCM can be used to evaluate time-varying causality in dynamic networks such as brain networks [49].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The convergence speeds of CCM and cCCM also vary with the signals under applications and need to be taken into consideration in causality analysis, especially in dynamic systems where the causal relationships are time-variant. It is worthy to point out that when combined with the sliding window approach [47,48], cCCM can be used to evaluate time-varying causality in dynamic networks such as brain networks [49].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Zhuang et al reported spinal cord stimulation may facilitate the recovery of consciousness, and they used an EEG test to predict the process [150]. Thanks to the boom in deep learning, many deep learning models are developed and combined with EEG to detect mental fatigue [151], Parkinson's disease [152], depression [153], schizophrenia [154,155], epilepsy [156][157][158], and neurocognitive disorders [159,160]. In addition to symptom detection, EEG is reported to localize the epileptogenic zone [161,162] and it has the potential to guide the surgery.…”
Section: Bioelectrical Sensorsmentioning
confidence: 99%